A new species of Leucostethus (Anura: Dendrobatidae) from the Cordillera Mache-Chindul in northwestern Ecuador, with comments on similar Colostethus and Hyloxalus - Vigle, Gregory O.; Coloma, Luis A.; Santos, Juan Carlos; Hernandez-Nieto, Sebastian; Ortega-Andrade, H. Mauricio; Paluh, Daniel J.; Read, Morley (Zootaxa, 2020)
We describe a new species of dendrobatid frog, Leucostethus bilsa sp. nov., using molecular, morphological, and acoustic evidence. We also comment on the taxonomic status of four similar Hyloxalus and Colostethus. We provide an updated phylogeny of Leucostethus that corroborates previous hypotheses of relationships of nine species. Phylogenetic analysis using mitochondrial (i.e., 7095 bp of combined data from NADH1, NAHD2, cytochrome c oxidase I, cytochrome b and 12S-16S rRNA) and seven nuclear genes (i.e., 4739 bp) indicate a close relationship of L. bilsa to an undescribed species from Gorgona Island, Colombia, both of which apparently diverged in the Pliocene about 3 million years ago with about 6.25% (i.e., 146/2335 bp) differences for the section of 12S-16S mitochondrial fragment. Leucostethus bilsa is diurnal and riparian, characterized by distinctive bright mustard-yellow flash marks in the axillar and groin regions, posterior belly, and in the hindlimbs, the presence of dark gray lower labial stripe or marks, sexual dimorphism in ventral pattern, and by having male uniparental care. We describe its osteology and the male advertisement call, which is a series of peep notes. Osteological microCT images of representatives of each of the Colostethinae genera reveal a number of intriguing characters that may prove to be useful in phylogenetic studies. In terms of its distribution, Leucostethus bilsa is currently known only from a very small area within the Reserva Biológica Bilsa, located within the Cordillera Mache-Chindul in the Chocoan region of northwestern Ecuador, which was a Pliocene-Pleistocene refugium. This region is highly threatened with habitat degradation and remains as the last surviving refuge for a forest community known for a high proportion of endemic species of both flora and fauna.